Initial Experience of Open Radical Retropubic Prostatecomy With 5 Cases - Belal, Md Towhid; Rahman, Md Mostafizur; Chowdhury, Tanvir Ahmed; Hossain, Md. Shamim; Chowdhury, Md Shafiqul Alam; Rasul, Md Amanur; Islam, Md Kamrul (KYAMC Journal, 2019)
Background: Radical prostatectomy is the best treatment option for clinically localized prostate cancer. But oncological as well as functional outcomes of this procedure including incontinence and erectile dysfunction are a big challenge for the surgeon. Objectives: This paper has focused on our initial experiences of oncological and functional outcomes of open radical retropubic prostatectomy. Materials and methods: Total five cases underwent open radical retropubic prostatectomy between January'2016 to October' 2017. All patients had clinically organ confined prostatic adenocarcinoma. Open radical retropubic prostatectomy with bilateral pelvic lymph node dissection was done through a lower midline incision. We observed the surgical experiences and assess the oncological and functional outcomes postoperatively. Results: The median age (range) of patients at diagnosis was 63 (56-72) years. The median Gleason sum (range) was 7 (6-9) and mean pretreatment PSA was 16.2±5.4 ng/ml. There was no perioperative mortality and no major complications in immediate postoperative period. Final pathological specimen shows negative surgical margin in all cases but one patient has positive unilateral lymph nodes. One patient achieved continence within 3 months; three patients achieved continence at 6 months, one patient after one year. Two patients had satisfactory erection at 6 months; onepatients are at 9 months, and two patients could not gain erection after one year. Conclusion: Though open radical retropubic prostatectomy is tough procedure due to its difficult access to the surgical field. Oncological and functional outcome is totally depending on the skill of the surgical team. KYAMC Journal Vol. 9, No.-4, January 2019, Page 166-169